Do five-star hotel managers know their customers' priorities? An AHP-Prioritised scorecard study. Issue 2 (1st July 2019) - Ishizaka, Alessio; Quintano, Alfred; Labib, Ashraf; Apostolakis, Alexandros
Abstract : Purpose: Regular surveys by the Malta Hotels & Restaurants Association indicate a substantial improvement in the financial performance of five-star hotels in Malta in recent years. Therefore, the purpose of this paper is to investigate if this positive performance is primarily due to customer centricity by management. Design/methodology/approach: The assessment is based on the findings of a quantitative study that compared the results of a demand side (customer survey) with those of a supply side (management survey). In total, 24 decision-choice criteria were framed within the four perspectives (financial, customer, internal process and employee learning/growth) of the balanced scorecard. Actual and potential customers of five-star hotels and hotel managers were asked to rank the decision-choice criteria and the balanced scorecard perspectives. The multi-criteria decision analysis was carried out by means of the AHP. Findings: The study showed that managers in the five-star hospitality sector in Malta are in harmony with customer expectations given the strong positive correlation between the results of the customer and management surveys. Research limitations/implications: This research is limited to the island of Malta but can be easily replicated for other touristic destinations. Practical implications: This study has implication for hospitality customers, hotel managers and policy makers to help them to identify weak areas of hotel performance and improve them. Originality/value: The paper has developed a Prioritised scorecard, a new hybrid balanced scorecard and AHP. Targets are therefore prioritised, which allow a better allocation of scarce resources.